2017
DOI: 10.12659/msm.905204
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Pretreatment Red Blood Cell Distribution Width in Patients with Newly Diagnosed Glioblastoma

Abstract: BackgroundRed blood cell distribution width (RDW) is a parameter of the complete blood count (CBC) test. Recent evidence suggests that pretreatment RDW is associated with patient survival in various malignant tumors. We explored the association of pretreatment RDW and other red blood cell (RBC) parameters with clinical parameters and assessed their prognostic impact on overall survival (OS) in patients with glioblastoma (GBM).Material/MethodsIn total, 109 patients with newly diagnosed GBM were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Higher RDW level indicates greater variation in the size of RBCs, which is associated with worse outcomes in patients with heart failure, stroke, head and neck cancer, and lung cancer. 41 In accordance with previous studies, 12,24 we found that higher RDW was associated with a poorer OS of patients with glioma (HR: 1.40; 95% CI: 1.13-1.74; P = 0.002). It is reported that RDW correlated with IL-6, tumor necrosis factor-alpha, and other circulating cytokines that can affect the tumor cell biological behavior.…”
Section: Complex Interactions Between Tumor Cells and Inflammatory Cysupporting
confidence: 91%
See 4 more Smart Citations
“…Higher RDW level indicates greater variation in the size of RBCs, which is associated with worse outcomes in patients with heart failure, stroke, head and neck cancer, and lung cancer. 41 In accordance with previous studies, 12,24 we found that higher RDW was associated with a poorer OS of patients with glioma (HR: 1.40; 95% CI: 1.13-1.74; P = 0.002). It is reported that RDW correlated with IL-6, tumor necrosis factor-alpha, and other circulating cytokines that can affect the tumor cell biological behavior.…”
Section: Complex Interactions Between Tumor Cells and Inflammatory Cysupporting
confidence: 91%
“…All of the included studies were published in recent years and were from seven different countries, which were retrospectively designed with 17 single‐center trialsand one multicenter trial . There were 15 studies performed multivariate Cox regression analysis and reported adjusted HR . The main features of the selected studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations